An optimum batch size for a production system operating under a continuous supply/demand - Sarker, M. Ruhul Amin; Karim, A.N. Mustafizul; Haque, A. F. M. Anwarul (1995)
A manufacturing system which procures raw materials from suppliers in a lot and processes them to convert to finished products is considered in this paper. An ordering policy is proposed for raw materials to meet the requirements of a production facility which, in turn, must deliver finished products demanded by outside consumers at constant rate. First, a general cost model is developed considering both raw materials and finished products. Then using this model a simple procedure is developed to determine an optimal ordering policy for procurement of raw materials, and the manufacturing batch size to minimize the total cost for meeting the customer demand in time. Numerical examples are also presented. I